Equal Pay for Equal Work – The Distributional Effects of the Assignment Policy for Military Women - Dieckmann, Christina M. (Columbia Journal of Gender and Law, 2011)
In September 2003, Captain Kellie McCoy was leading a platoon of soldiers in a four-truck convoy on an Iraqi highway between Fallujah and Ramadi when her platoon was ambushed. The lead truck hit an Improvised Explosive Device (lED) as another lED detonated behind it. The enemy rushed the convoy from both sides of the road, firing at the trucks with rifles and rocket-propelled grenades. Captain McCoy’s Humvee was the only one that survived the attack; the other three vehicles were badly damaged by the bombs and by small arms fire, and several of the soldierswere wounded. With cover only from the rooftop gunner and her own M-4 carbine, Captain McCoy managed to rescue all of the men from the other trucks while under continuous fire from the attackers, eventually driving the four- seat Humvee loaded with twelve passengers to safety. For her actions that afternoon, Captain McCoy was awarded the Bronze Star.